Modeling and Optimization of Frequency Tunable Piezoelectric Micro Power Generator - Alrashdan, Mohd H.S.; Ahmed, Mohammad Z.; Abu-Al-Aish, Amir (Micro and Nanosystems, 2017)
Background: Piezoelectric micro-power generator (PMPG) is used to scavenge mechanical vibration energy and convert it into electrical energy via piezoelectric effects. In tire-pressure monitoring system (TPMS), the utilization of PMPG eliminates the requirement for a traditional battery replacement. Objective: In this paper, a PMPG was designed and optimized in the frequency range of 900-1100 Hz. Method: A Taguchi optimization method based on Orthogonal arrays (OA) and signal-to-noise (S/N) ratio is used in order to design a PMPG that vibrates at 1 kHz. The PMPG model selected to be cantilever beam cross shape with seven control factors which are strip length, strip width, strip displacement from the origin, membrane material, piezo material, membrane thickness and piezo thickness. The resonance eigenfrequency and transient analysis are conducted for the optimized PMPG model using COMSOL Multiphysics software. Result: The analyzed results show that there are three main factors that play the major role in PMPG optimization. These factors are, in descending order, membrane thickness, strip displacement from the origin and strip width. The first resonance eigen frequency found at 1 kHz, with peak voltage of 0.012 V, and reached the steady state after 0.03 seconds. The PMPG presented in this work is able to power a large number of small electronic devices like TPMS at 1 KHz. Furthermore, this optimization method solved tuning problems associated with PMPG cross shape rectangular cantilever beam.
Keywords: PMPG